Original Experience of Transaortic Approach in Bivalve Replacement - I. I. Chernov; S. T. Enginoev; D. A. Kondratiev; A. A. Ziankou; D. G. Tarasov (Креативная хирургия и онкология)
Background. Combined valve lesions affect more than one valve, which may hamper a correct estimation of the individual valve severity. The study aimed to assess the outcome of transaortic mitral valve replacement (TAMVR) in a bivalve replacement procedure.Materials and methods. A retrospective study was conducted with 19 patients having TAMVR during bivalve replacement. The mean patient age was 58 ± 8.6 years, including 10 male patients. Diabetes mellitus was diagnosed in 3 patients, atrial fibrillation — in 14, coronary heart disease — in 2, chronic obstructive pulmonary disease — in 2, stroke in history — in 1, chronic heart failure stage 3–4 (NYHA) — in 19 patients.  Infectious endocarditis as the disease aetiology was found in 4 patients. Two patients had previous heart surgery. Echocardiography: mean left ventricular ejection fraction 55 ± 7.3 %, mean pulmonary artery pressure 47 ± 13.7 mm Hg, median aortic valve fibrous ring diameter 23 (21–25) mm.Results and discussion. Mechanical replacement was performed in 12 cases. Median surgery time was 160 (150–185) min, median myocardial ischaemia (MI) time — 67 ± 9.7 min and artificial circulation (AC) time — 87 ± 12.5 min. Resternotomy for bleeding was performed in 2 patients, with median postoperative blood loss  300 (212–587) mL. Early postoperative delirium developed in 4 patients, acute renal failure requiring  haemodialysis — in 1 patient. Stroke, perioperative myocardial damage and conduction disorder requiring pacemaker implantation not observed in postoperative period. Median artificial lung ventilation time (ALV) was 9.5 (6–15) h, ≥24 h — in two cases. One lethal early postoperative case was registered.Conclusion. TAMVR in a bivalve replacement setting is a safe technique with short AC, MI and surgery times and can be recommended in patients with a wide aortic valve fibrous ring.